2019
DOI: 10.1177/0886260519889932
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Disclosing Childhood Victimization and Risk of Revictimization in Young Adulthood

Abstract: Experiencing victimization in childhood increases risk of adulthood revictimization, and it is important to understand what may contribute to such risk. One factor that may help to explain the increased risk of future victimization is disclosure. However, the literature is mixed as to whether disclosure of prior victimization is helpful for protecting against adverse outcomes, and much of the research on disclosure focuses solely on sexual victimization. The current study examines the relationship between vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Thus, even when coexisting alongside positive childhood experiences, negative childhood experiences seem to have a greater impact on adversity in adulthood. In fact, previous studies revealed that abuse during childhood may be related to sexual abuse (Ports, Ford, & Merrick, 2016), intimate partner abuse (Riedl et al, 2019), and other forms of victimization in adulthood (Desir & Karatekin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even when coexisting alongside positive childhood experiences, negative childhood experiences seem to have a greater impact on adversity in adulthood. In fact, previous studies revealed that abuse during childhood may be related to sexual abuse (Ports, Ford, & Merrick, 2016), intimate partner abuse (Riedl et al, 2019), and other forms of victimization in adulthood (Desir & Karatekin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study with college students indicated that of those reporting a history of childhood victimization such as maltreatment, only 53.3% had ever told someone about their experiences and if they did, they were more likely to first disclose to a parent or friend. Only 20.8% had first disclosed to a professional, suggesting that if disclosure does happen, it often happens to informal sources (Desir & Karatekin, 2019). Preference to avoid thinking about maltreatment could also certainly be the case for individuals who have avoidance symptoms of PTSD, feel unsafe or invalidated in the disclosure context, or perceive themselves as vulnerable in other ways because of having minoritized identities, being pregnant, or having low social support (Narayan et al, 2017;Herman, 2003).…”
Section: Recommendations Against Invalidating Terminologymentioning
confidence: 99%
“…Importantly, these revictimization rates account for the presence of any secondary trauma, regardless of form. For example, while it is true that sexual victimization in childhood doubles a person’s risk for sexual victimization in adulthood, experiencing physical abuse and witnessing violence in childhood can also increase the risk of adult sexual victimization (Desir & Karatekin, 2021; Tjaden & Thoennes, 2000). Because of its high rates of revictimization and differential impact on survivors, research on sexual trauma is frequently examined separately from other forms of trauma (Barnes et al, 2009; Contractor et al, 2020).…”
Section: Sex Behaviors and Attitudesmentioning
confidence: 99%